2020
DOI: 10.1152/japplphysiol.00355.2019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of thermal treatments after lengthening contraction on mechanical hyperalgesia and exercise-induced physiological changes in rat muscle

Abstract: Delayed-onset muscle soreness (DOMS) is a common but displeasing event induced by excessive muscle use or unaccustomed exercise and characterized by tenderness and movement-related pain in the exercised muscle. Thermal therapies, either icing or heating applied to muscles immediately after exercise, have been used as therapeutic interventions for DOMS. However, the mechanisms of their analgesic effects, and physiological and metabolic changes in the muscle during thermal therapy, remain unclear. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The use of an animal model is particularly advantageous in this case because blinding humans to thermal treatments is difficult and the potential for bias when assessing subjective parameters, such as pain, is elevated. This study revealed that, contrary to icing, local HT applied to the gastrocnemius muscle for 20 min using a gel pack markedly attenuated mechanical hyperalgesia (77). Further, the levels of several metabolites, including nicotinamide and N⁵-ethyl-L-glutamine, were altered by HT, indicating that the analgesic effects of local heat stress may be partially derived from changes in metabolism (77).…”
Section: Delayed-onset Muscle Sorenessmentioning
confidence: 83%
See 2 more Smart Citations
“…The use of an animal model is particularly advantageous in this case because blinding humans to thermal treatments is difficult and the potential for bias when assessing subjective parameters, such as pain, is elevated. This study revealed that, contrary to icing, local HT applied to the gastrocnemius muscle for 20 min using a gel pack markedly attenuated mechanical hyperalgesia (77). Further, the levels of several metabolites, including nicotinamide and N⁵-ethyl-L-glutamine, were altered by HT, indicating that the analgesic effects of local heat stress may be partially derived from changes in metabolism (77).…”
Section: Delayed-onset Muscle Sorenessmentioning
confidence: 83%
“…This study revealed that, contrary to icing, local HT applied to the gastrocnemius muscle for 20 min using a gel pack markedly attenuated mechanical hyperalgesia (77). Further, the levels of several metabolites, including nicotinamide and N⁵-ethyl-L-glutamine, were altered by HT, indicating that the analgesic effects of local heat stress may be partially derived from changes in metabolism (77).…”
Section: Delayed-onset Muscle Sorenessmentioning
confidence: 83%
See 1 more Smart Citation
“…These improvements occurred without any significant alterations in calf muscle oxygenation, which indicates that alternative mechanisms underlie the improvements in walking tolerance. One possibility is that HT‐induced analgesia (Tsuboshima et al., 2020) evoked an increase in pain tolerance, thereby enabling an increase in PWT.…”
Section: Discussionmentioning
confidence: 99%
“…Local heat therapy (HT) is one promising approach to hasten the recovery of muscle function (8,9) and combat the mechanical hyperalgesia associated with exercise-induced muscle damage (10). We and others demonstrated that local HT promotes the expression in human skeletal muscle of factors involved in angiogenesis (11,12), stress management (12) and mitochondrial biogenesis (13,14).…”
mentioning
confidence: 99%